(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper we suggest an efficient compression and encoding coding performance based on Integer multi wavelet transform of medical application. This method reduces the Mean Square coefficients and increases the peak signal to noise ratio in the code block due to the transmission purpose. By using this coding technique the compressed data and encoded bit stream are all suited for progressive transmission. By the experimental results show that the proposed algorithm gives better quality, if the images using integer multi wavelets compared to that of the other wavelets transforms. The parameter of the system has been evaluated based on Compression Ratio (CR), peak signal to noise ratio (PSNR) and mean square error (MSE).